Interlanguage features of adult learners’ continuous writing: implications for adult literacy teaching (2009)
Communication is an indispensable activity in the lives of individuals in society. For proper communication to take place, language as a tool for communication must be adequately developed. Adults and adult learners are constantly in the process of communication, given the various roles they play in society. As a result of varying levels of educational attainment, some adult learners have developed defective interlanguage patterns that have not affected their roles positively. This paper examines the features of adult learners’ interlanguage among some Diploma students in the University of Ibadan. Through the use of descriptive research design and random sampling, a group of adult learners’ continuous writing skills were examined. Findings revealed that some adult learners lack syntactic competence and mechanical accuracy in their writings. The study, among other things recommends that adult learners be exposed to good literature as well as constant practice in grammar.